Gene expression profile of human follicle dermal papilla cells in response to Camellia japonica phytoplacenta extract. Issue 3 (14th February 2021) - Cho, Won Kyong; Kim, Hye‐In; Paek, Seung Hye; Kim, Soo‐Yun; Hyun Seo, Hyo; Song, Jihyeok; Lee, Ok Hwa; Min, Jiae; Lee, Sang Jun; Jo, Yeonhwa; Choi, Hoseong; Lee, Jeong Hun; et al.
Abstract : Camellia japonica L. is a flowering tree with several medicinal and cosmetic applications. Here, we investigated the efficacy of C. japonica placenta extract (CJPE) as a potential therapeutic agent for promotion of hair growth and scalp health by using various in vitro and in vivo assays. Moreover, we performed transcriptome analysis to examine the relative expression of human follicle dermal papilla cells (HFDPC) in response to CJPE by RNA‐sequencing (RNA‐seq). In vitro assays revealed upregulation of the expression of hair growth marker genes in HFDPC after CJPE treatment. Moreover, in vivo clinical tests with 42 adult female participants showed that a solution containing 0.5% CJPE increased the moisture content of the scalp and decreased the scalp's sebum content, dead scalp keratin, and erythema. Furthermore, RNA‐seq analysis revealed key genes in HFDPC which are associated with CJPE. Interestingly, genes associated with lipid metabolism and cholesterol efflux were upregulated. Genes upregulated by CJPE are associated with several hormones, including parathyroid, adrenocorticotropic hormone, α‐melanocyte‐stimulating hormone (alpha‐MSH), and norepinephrine, which are involved in hair follicle biology. Furthermore, some upregulated genes are associated with the regulation of axon guidance. In contrast, many genes downregulated by CJPE are associated with structural components of the cytoskeleton. In addition, CJPE suppressed genes associated with muscle structure and development. Taken together, this study provides extensive evidence that CJPE may have potential as a therapeutic agent for scalp treatment and hair growth promotion. Abstract : Here, we examined the efficacy of C. japonica placenta extract (CJPE) as a potential therapeutic agent for promotion of hair growth and scalp health by using various in vitro and in vivo assays. Moreover, we conducted transcriptome analysis to examine the relative expression of human follicle dermal papilla cells in response to CJPE by RNA‐sequencing.